West Nile Virus in Slovenia - Nataša Knap; Miša Korva; Vladimir Ivović; Katja Kalan; Mateja Jelovšek; Martin Sagadin; Samo Zakotnik; Katja Strašek Smrdel; Jan Slunečko; Tatjana Avšič-Županc (Viruses, 2020)
West Nile virus (WNV) is a flavivirus transmitted by mosquitoes. Birds are the reservoir for the virus; humans, horses and other mammals are dead-end hosts. Infections caused by WNV in humans can vary from asymptomatic infections to West Nile fever (WNF) or West Nile neuroinvasive disease (WNND). In 1995, a serosurvey was performed in Slovenia on forest workers, and WNV specific IgG antibodies were confirmed in 6.8% of the screened samples, indicating that WNV is circulating in Slovenia. No human disease cases were detected in Slovenia until 2013, when the first case of WNV infection was confirmed in a retrospective study in a 79-year old man with meningitis. In 2018, three patients with WNND were confirmed by laboratory tests, with detection of IgM antibodies in the cerebrospinal fluid of the patients. In one of the patients, WNV RNA was detected in the urine sample. In 2017, 2018 and 2019, a mosquito study was performed in Slovenia. Mosquitoes were sampled on 14 control locations and 35 additional locations in 2019. No WNV was detected in mosquitoes in 2017 and 2019, but we confirmed the virus in a pool of Culex sp. mosquitoes in 2018. The virus was successfully isolated, and complete genome sequence was acquired. The whole genome of the WNV was also sequenced from the patient’s urine sample. The whole genome sequences of the WNV virus detected in Slovenian patient and mosquito indicate the virus most likely spread from the north, because of the geographic proximity and because the sequences cluster with the Austrian and Hungarian sequences. A sentinel study was performed on dog sera samples, and we were able to confirm IgG antibodies in 1.8% and 4.3% of the samples in 2017 and 2018, respectively. Though Slovenia is not a highly endemic country for WNV, we have established that the virus circulates in Slovenia.